A method for preparing a microstructured broadband wave-transmitting ceramic shaped part

By using a 3D printing method with specific formulation and process control, a broadband transparent ceramic irregular part with microstructure was successfully prepared, which solved the problem that it is difficult to print large tilt angle cantilever structures with existing technology. It achieved efficient and low-cost multi-band wave transmission performance, which meets the needs of new missile weapon systems.

CN118206366BActive Publication Date: 2025-01-28HARBIN INST OF TECH +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410434507.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-01-28
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

Existing 3D printing methods are difficult to use multiphase transparent ceramic materials to print broadband transparent irregular parts with large tilt angle cantilever structures. In addition, traditional manufacturing methods are costly and time-consuming, making it difficult to meet the requirements of new missile weapon systems for high temperature resistance, multi-frequency bands, and wide bandwidth.

Method used

A mixture of inorganic microwave-transparent ceramic powder, thickener, elastomer, lubricant and antioxidant with a specific formulation is used for 3D printing. By controlling the nozzle, heated bed and cooling rate, a ceramic blank with microstructure is printed. Solvent degreasing and thermal degreasing sintering are then performed to form a broadband microwave-transparent ceramic irregular part with a three-dimensional boss structure.

Benefits of technology

It has achieved integrated molding of complex-shaped broadband transparent ceramic samples with high transmittance and stable properties. It can efficiently transmit waves in the frequency range of 15.5GHz to 18.5GHz, and is low in cost and short in cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118206366B_ABST
    Figure CN118206366B_ABST
Patent Text Reader

Abstract

A method for preparing a broadband wave-transmitting ceramic shaped part containing a microstructure belongs to the technical field of wave-transmitting ceramics. The present invention aims to solve the problem that the existing 3D printing method is difficult to use multi-phase wave-transmitting ceramic materials to 3D print broadband wave-transmitting shaped parts containing a large tilt angle cantilever structure. Method: 1. Weighing raw materials; 2. Preparation of 3D printing ceramic raw materials; 3. 3D printing; 4. Degreasing and sintering. The present invention is used for the preparation of broadband wave-transmitting ceramic shaped parts containing microstructures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave-transmitting ceramics. Background Art

[0002] With the rapid development of aerospace technology, microwave communication technology and modern anti-radiation missile seeker technology, various types of ultra-high-speed aircraft not only put forward high temperature resistance requirements for electromagnetic windows, but also require the seeker to work in a wide frequency band. The main function of the radome is to protect the antenna inside the cover to ensure the normal operation of communication, telemetry, guidance, detonation and other systems in harsh environments, and it plays the functions of heat protection, load bearing and wave transmission. The traditional radome preparation technology has a single working frequency and a narrow frequency band, and is often easily intercepted during terminal guidance. In order to meet the needs of attacking radars of all parties (such as low-frequency warning radars, high-frequency missile guidance, high-frequency gun aiming radars, etc.), higher requirements are put forward for the high penetration capability of new anti-radiation missile weapons, requiring the radome to meet the working frequency coverage of 0.1GHz to 40GHz. The development of high-temperature resistant, multi-band, and wide-band wave-transparent materials is increasingly becoming a new trend and important technology in the development of new missile weapon systems.

[0003] Traditional methods for preparing radomes usually include grouting and gel casting, which can achieve near-net-size forming of radomes, but the custom mold increases the economic cost. In addition, the process also includes demoulding, degreasing and finishing steps. In this way, a radome shape with the same shape as the cavity and adjustable thickness can be prepared. The radome prepared in this way is evenly stressed everywhere, but it can only be used to prepare radomes with simple and uniform shapes, with poor functionality and high time cost.

[0004] In order to achieve broadband wave-transmitting performance, it is usually necessary to design the radome into a porous gradient structure, a sandwich structure, or to design a microstructure on the surface of the radome. However, the design methods and preparation methods of broadband wave-transmitting ceramic shaped parts described in existing patents and literature have some shortcomings and limitations in terms of material applicability, performance, process and cost. Especially when using 3D printing, it is difficult to meet the following two conditions at the same time: 1. Printing multi-phase toughened wave-transmitting ceramic materials; 2. Printing large-sized wave-transmitting shaped parts containing three-dimensional boss structure layers. Therefore, it is urgent to develop low-cost, short-cycle, reliable performance wave-transmitting ceramic sample / radome preparation technology suitable for different wave-transmitting material systems. Summary of the invention

[0005] The present invention aims to solve the problem that the existing 3D printing method is difficult to use multi-phase wave-transmitting ceramic materials to 3D print broadband wave-transmitting special-shaped parts containing large tilt angle cantilever structures, and further provide a preparation method of broadband wave-transmitting ceramic special-shaped parts containing microstructures.

[0006] A method for preparing a microstructured broadband wave-transmitting ceramic shaped part is carried out according to the following steps:

[0007] 1. Weighing of raw materials:

[0008] Weigh 70 to 85 parts of inorganic wave-transmitting ceramic powder, 0 to 15 parts of tackifier, 0 to 10 parts of elastomer, 5 to 15 parts of lubricant, 0.1 to 1 part of antioxidant and 0.5 to 5 parts of coupling agent according to mass proportion;

[0009] 2. Preparation of 3D printing ceramic raw materials:

[0010] ① The inorganic wave-transmitting ceramic powder and the coupling agent are ball-milled, mixed and dried to obtain a mixture A;

[0011] ② Mix the weighed tackifier, elastomer, lubricant and antioxidant by internal kneading to obtain a mixture B;

[0012] ③ Adding mixture A to mixture B in 3 to 5 times, and performing banburying mixing after each addition to obtain a banburying material;

[0013] ④ The mixed materials are extruded through an extruder, and cut after water cooling or air cooling to obtain pellets;

[0014] 3. 3D printing:

[0015] Under the conditions of nozzle diameter of 0.4 mm to 0.8 mm, nozzle temperature of 120° C. to 190° C., hot bed temperature of 50° C. to 90° C., cooling rate of 15° C. / min to 30° C. / min, and printing speed of 20 mm / s to 60 mm / s, 3D printing is performed using pellets to obtain a ceramic body containing a microstructure;

[0016] The ceramic body containing microstructure is specifically composed of a substrate and a three-dimensional boss structure, and the three-dimensional boss structure is arranged on the surface of the substrate;

[0017] 4. Degreasing and sintering:

[0018] The ceramic green body containing the microstructure is subjected to solvent degreasing, thermal degreasing and sintering in sequence to obtain a broadband wave-transmitting ceramic special-shaped part containing the microstructure.

[0019] The beneficial effects of the present invention are:

[0020] 1. The present invention designs a wave-transmitting material formula for fused deposition 3D printing, which has stable properties, high solid content and good rheological properties.

[0021] 2. The formula designed in the present invention can realize the printing of the three-dimensional boss microstructure set on the side surface from bottom to top, and the span of the three-dimensional boss is large (that is, the maximum size of the boss protruding relative to the side surface can reach 6mm) and the inclination angle (40-60°) is large.

[0022] 3. The present invention can realize the integrated molding of broadband wave-transmitting ceramic samples with complex surfaces (including three-dimensional microstructure layers), and has a high wave transmittance in the frequency range of 15.5 GHz to 18.5 GHz.

[0023] Instruction Manual

[0024] Figure 1 The shear rate-viscosity curve of the pellets prepared in step 2 of Example 1 at 170°C;

[0025] Figure 2 This is the shear strain-modulus diagram of the pellets prepared in step 2 of Example 1 at 170°C;

[0026] Figure 3 Schematic diagram of the structure of the ceramic body containing microstructure prepared in step 3 of Example 1, a is a schematic diagram of the overall structure, and b is a side view;

[0027] Figure 4 This is a schematic diagram of the printing direction of step three of embodiment 1;

[0028] Figure 5 This is the thermal degreasing curve of step 4 of Example 1;

[0029] Figure 6 The actual pictures are of the ceramic green body with microstructure prepared in step 3 of Example 1 and the broadband wave-transmitting ceramic shaped piece with microstructure prepared in step 4, a-1 is the ceramic green body, a-2 is the ceramic shaped piece after solvent degreasing, thermal degreasing and sintering of a-1, b-1 is the ceramic green body, b-2 is the ceramic shaped piece after solvent degreasing, thermal degreasing and sintering of b-1;

[0030] Figure 7 The XRD spectrum of the broadband wave-transmitting ceramic shaped piece containing microstructure prepared in step 4 of Example 1;

[0031] Figure 8 This is a SEM image of the broadband wave-transmitting ceramic shaped piece containing a microstructure prepared in step 4 of Example 1;

[0032] Fig. 9 : The wave transmission rate comparison diagram, (a) is the flat wave-transmitting ceramic piece prepared in the comparative experiment 1; (b) is the special-shaped ceramic piece with microstructure and broadband wave-transmitting prepared in step 4 of the embodiment 1;

[0033] Fig.10 The three-dimensional renderings of the broadband wave-transmitting ceramic shaped part containing microstructure prepared in step 4 of Example 8 are as follows, (a) is a side sectional view, (b) is a cross sectional view, (c) is a bottom view, (d) is a front view, and (e) is a top view. DETAILED DESCRIPTION

[0034] Specific implementation method 1: This implementation method is a method for preparing a microstructured broadband wave-transmitting ceramic shaped part, which is carried out according to the following steps:

[0035] 1. Weighing of raw materials:

[0036] Weigh 70 to 85 parts of inorganic wave-transmitting ceramic powder, 0 to 15 parts of tackifier, 0 to 10 parts of elastomer, 5 to 15 parts of lubricant, 0.1 to 1 part of antioxidant and 0.5 to 5 parts of coupling agent according to mass proportion;

[0037] 2. Preparation of 3D printing ceramic raw materials:

[0038] ① The inorganic wave-transmitting ceramic powder and the coupling agent are ball-milled, mixed and dried to obtain a mixture A;

[0039] ② Mix the weighed tackifier, elastomer, lubricant and antioxidant by internal kneading to obtain a mixture B;

[0040] ③ Adding mixture A to mixture B in 3 to 5 times, and performing banburying mixing after each addition to obtain a banburying material;

[0041] ④ The mixed materials are extruded through an extruder, and cut after water cooling or air cooling to obtain pellets;

[0042] 3. 3D printing:

[0043] Under the conditions of nozzle diameter of 0.4 mm to 0.8 mm, nozzle temperature of 120° C. to 190° C., hot bed temperature of 50° C. to 90° C., cooling rate of 15° C. / min to 30° C. / min, and printing speed of 20 mm / s to 60 mm / s, 3D printing is performed using pellets to obtain a ceramic body containing a microstructure;

[0044] The ceramic body containing microstructure is specifically composed of a substrate and a three-dimensional boss structure, and the three-dimensional boss structure is arranged on the surface of the substrate;

[0045] 4. Degreasing and sintering:

[0046] The ceramic green body containing the microstructure is subjected to solvent degreasing, thermal degreasing and sintering in sequence to obtain a broadband wave-transmitting ceramic special-shaped part containing the microstructure.

[0047] In the process of thermal debinding, in order to prevent the 3D printed body from structural collapse or cracking, the pre-embedded powder of the body is degreased to maintain the shape of the ceramic body and accelerate the removal of polymers by using the capillary force of the pre-embedded powder.

[0048] The beneficial effects of this embodiment are:

[0049] 1. This embodiment designs a wave-transmitting material formula for fused deposition 3D printing, which has stable properties, high solid content and good rheological properties.

[0050] 2. The formula designed in this embodiment can realize the printing of the three-dimensional boss microstructure set on the side surface from bottom to top, and the span of the three-dimensional boss is large (that is, the maximum size of the boss protruding relative to the side surface can reach 6mm) and the inclination angle (40-60°) is large.

[0051] 3. This embodiment can realize the integrated molding of broadband wave-transmitting ceramic samples with complex surfaces (including three-dimensional microstructure layers), and has a high wave transmittance in the frequency range of 15.5 GHz to 18.5 GHz.

[0052] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the inorganic wave-transmitting ceramic powder described in step 1 is a mixture of ceramic powder and additive powder; the ceramic powder is a mixture of one or two of fused quartz and silicon nitride; the additive powder is one or a mixture of several of aluminum oxide, yttrium oxide, boron nitride and microcrystalline glass powder; the mass ratio of the additive powder to the ceramic powder is 1:(8-12); the median diameter of the inorganic wave-transmitting ceramic powder is 200 nanometers to 3 micrometers, and the particle size span is 2-7. Others are the same as specific implementation method 1.

[0053] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the tackifier described in step 1 is one or a mixture of polyethylene, polypropylene, polystyrene, polyester resin and polylactic acid. The rest is the same as specific implementation method 1 or 2.

[0054] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the elastomer described in step 1 is one or a mixture of ethylene-vinyl acetate copolymer, ethylene propylene diene monomer rubber and ethylene-octene copolymer. Others are the same as specific embodiments 1 to 3.

[0055] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the lubricant in step 1 is one of polyethylene wax, polypropylene wax, stearic acid amide, oleic acid amide, paraffin, stearic acid and n-butyl stearate or a mixture of several of them. The rest is the same as specific embodiments 1 to 4.

[0056] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the antioxidant described in step 1 is one of 2,6-di-tert-butyl-4-methylphenol, octylated diphenylamine and antioxidant 2246 or a mixture of several thereof; the coupling agent described in step 1 is one of γ-aminopropylmethyldimethoxysilane, isopropyl trioleate titanate, di(octylphenol polyoxyethylene ether) phosphite and 3-methacryloxypropyltrimethoxysilane or a mixture of several thereof. Others are the same as specific embodiments 1 to 5.

[0057] Specific embodiment 7: This embodiment is different from any one of the specific embodiments 1 to 6 in that: the content of inorganic wave-transmitting ceramic powder in the granules described in step 2④ is 70wt.% or more; at a shear rate of 8s -1 and the temperature is 120 ℃ ~ 190 ℃, the viscosity of the pellets is lower than 2000 Pa · s, and the shear strain γ corresponding to the intersection of the storage modulus G' and the loss modulus G" of the pellets is less than 0.1 under the condition of temperature of 120 ℃ ~ 190 ℃. The rest is the same as the specific embodiments 1 to 6.

[0058] Specific embodiment eight: This embodiment is different from specific embodiments one to seven in that: the ball milling mixing described in step two ① specifically uses anhydrous ethanol as the grinding medium, and the ball milling mixing is 1h to 8h under the conditions of a ball-to-material ratio of (1 to 6): 1 and a rotation speed of 200r / min to 400r / min; the banburying mixing described in step two ② specifically adds it to a polymer banbury mixer, and banburying it for 30min to 60min under the conditions of a banburying temperature of 130℃ to 160℃ and a stirring speed of 100r / min to 200r / min; the banburying mixing described in step two ③ specifically mixes it for 10min to 30min under the conditions of a temperature of 130℃ to 160℃ and a stirring speed of 100r / min to 200r / min; the pellet diameter described in step two ④ is 2.7mm to 2.9mm, and the length is 3mm to 4mm. Others are the same as specific embodiments one to seven.

[0059] Specific embodiment nine: This embodiment is different from any one of specific embodiments one to eight in that: the substrate described in step three is in the shape of a flat plate, a hollow cone with an open bottom, a hollow hemisphere with an open bottom, or a curved plate; the three-dimensional boss structure described in step three is a tetrahedron, a tetrahedron, a truncated cone, or a curved boss; the thickness of the substrate in the microstructured broadband wave-transmitting ceramic shaped part prepared in step four is 1 mm to 30 mm; when the three-dimensional boss structure described in step three is a tetrahedron, and the top and bottom projections of the tetrahedron are both squares, the bottom projection square side length of the tetrahedron in the microstructured broadband wave-transmitting ceramic shaped part prepared in step four is 4 mm to 7 mm, the top projection square side length is 1.5 mm to 4.5 mm, and the bottom projection square side length ≥ the top projection square side length, and the height is 3 mm to 6 mm, the gap between the bottoms of adjacent tetrahedral pyramids is 1mm to 4mm; when the three-dimensional boss structure described in step 3 is a tetrahedral pyramid, and the bottom projection of the tetrahedral pyramid is a square, the bottom projection square of the tetrahedral pyramid in the microstructure broadband wave-transmitting ceramic shaped part prepared in step 4 has a side length of 4mm to 7mm, a height of 3mm to 6mm, and the gap between the bottoms of adjacent tetrahedral pyramids is 1mm to 4mm; when the three-dimensional boss structure described in step 3 is a truncated cone, and the top and bottom projections of the truncated cone are both circular, the bottom projection circular diameter of the circle in the microstructure broadband wave-transmitting ceramic shaped part prepared in step 4 is 4mm to 7mm, the top projection circular diameter is 1.5mm to 4.5mm, and the bottom projection circular diameter ≥ the top projection circular diameter, the height is 3mm to 6mm, and the gap between the bottoms of adjacent truncated cones is 1mm to 4mm. The rest is the same as the specific embodiments one to eight.

[0060] Specific embodiment 10: This embodiment is different from specific embodiments 1 to 9 in that: the solvent degreasing described in step 4 is specifically immersed in a solvent, and the degreasing is performed for 1 to 3 days at a solvent degreasing temperature of 25°C to 60°C; the solvent is one or a mixture of ethanol, isopropanol, ethyl acetate, kerosene, cyclohexane and toluene; the thermal degreasing described in step 4 is specifically embedded in the green body with sintering powder, and the thermal degreasing is performed for 24h to 72h at a degreasing temperature of 200°C to 600°C; the sintering described in step 4 is specifically sintered for 2h to 5h at a sintering temperature of 1200°C to 2000°C. The rest is the same as specific embodiments 1 to 9.

[0061] The following examples are used to verify the beneficial effects of the present invention:

[0062] Embodiment 1:

[0063] A method for preparing a microstructured broadband wave-transmitting ceramic shaped part is carried out according to the following steps:

[0064] 1. Weighing of raw materials:

[0065] Weigh 72 parts of inorganic wave-transmitting ceramic powder, 12.0 parts of tackifier, 2.3 parts of elastomer, 12.2 parts of lubricant, 0.5 parts of antioxidant and 1 part of coupling agent according to mass proportion;

[0066] 2. Preparation of 3D printing ceramic raw materials:

[0067] ① The inorganic wave-transmitting ceramic powder and the coupling agent are ball-milled, mixed and dried to obtain a mixture A;

[0068] ② Mix the weighed tackifier, elastomer, lubricant and antioxidant by internal kneading to obtain a mixture B;

[0069] ③ Adding mixture A to mixture B in three times, and performing banburying mixing after each addition to obtain a banburying material;

[0070] ④ The mixed materials are extruded through an extruder, and cut after water cooling to obtain pellets;

[0071] The content of inorganic wave-transmitting ceramic powder in the granules is 72wt.%; at a shear rate of 8s -1 At a temperature of 170°C, the viscosity of the pellets is 1230 Pa·s, and at a temperature of 170°C, the shear strain γ corresponding to the intersection of the storage modulus G' and the loss modulus G" of the pellets is 0.09;

[0072] 3. 3D printing:

[0073] Under the conditions of nozzle diameter of 0.8 mm, nozzle temperature of 165°C, hot bed temperature of 70°C, cooling rate of 25°C / min to 30°C / min and printing speed of 60 mm / s, 3D printing was performed using pellets to obtain a ceramic body containing a microstructure;

[0074] The ceramic body containing microstructure is specifically composed of a substrate and a three-dimensional boss structure, and the three-dimensional boss structure is arranged on the surface of the substrate; the substrate is in a flat plate shape; the three-dimensional boss structure is a quadrangular pyramid, the top and bottom projections of the quadrangular pyramid are both square, and the printing direction is printing along the length direction of the substrate;

[0075] 4. Degreasing and sintering:

[0076] The ceramic green body containing the microstructure is subjected to solvent degreasing, thermal degreasing and sintering in sequence to obtain a broadband wave-transmitting ceramic special-shaped part containing the microstructure;

[0077] The thickness of the matrix in the prepared microstructure-containing broadband wave-transmitting ceramic shaped parts is 1.2mm; the side length of the bottom projection square of the tetrahedron in the prepared microstructure-containing broadband wave-transmitting ceramic shaped parts is 5.73mm, the side length of the top projection square is 1.65mm, the height of the tetrahedron is 4.0mm, and the gap between the bottoms of adjacent tetrahedrons is 1.33mm.

[0078] The inorganic wave-transmitting ceramic powder described in step one is a mixture of ceramic powder and additive powder; the ceramic powder is fused quartz; the additive powder is boron nitride, and the mass ratio of the additive powder to the ceramic powder is 1:10; the median diameter of the inorganic wave-transmitting ceramic powder is 1 micron, and the particle size span is 2.8; the particle size span is specifically calculated according to the following formula: Sw=2.56 / [log(D90 / D10)], wherein Sw is the particle size span, D90 is the particle size corresponding to 90% of the cumulative particle size distribution of the sample, D90=2.4 microns, and D10 is the particle size corresponding to 10% of the cumulative particle size distribution of the sample, D10=0.3 microns.

[0079] The tackifier described in step one is polypropylene.

[0080] The elastomer described in step 1 is a mixture of ethylene-vinyl acetate copolymer and ethylene-octene copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to ethylene-octene copolymer is 1:1;

[0081] The lubricant described in step 1 is paraffin, and the melting point is 48 ℃~50 ℃.

[0082] The antioxidant described in step 1 is 2,6-di-tert-butyl-4-methylphenol.

[0083] The coupling agent described in step 1 is γ-aminopropylmethyldimethoxysilane.

[0084] The ball milling mixing described in step 2① is specifically to use anhydrous ethanol as the grinding medium, and the ball-to-material ratio is 2:1 and the rotation speed is 200r / min, and the ball milling mixing is 4h; the banburying mixing described in step 2② is specifically to add it to a polymer banburying machine, and banburying it for 30min at a banburying temperature of 140°C and a stirring speed of 150r / min; the banburying mixing described in step 2③ is specifically to mix it for 20min at a temperature of 140°C and a stirring speed of 100r / min; the pellets described in step 2④ have a diameter of 2.85mm and a length of 3mm.

[0085] The solvent degreasing in step 4 is specifically to immerse in a solvent, and degrease for 1 day at a solvent degreasing temperature of 60° C.; the solvent is cyclohexane;

[0086] The thermal degreasing described in step 4 specifically uses alumina sintering powder to pre-embed the green body, under air atmosphere and normal pressure, the temperature is raised from room temperature to 250°C in 50 minutes, kept at 250°C for 120 minutes, raised to 320°C in 70 minutes, kept at 320°C for 120 minutes, raised to 400°C in 80 minutes, kept at 400°C for 120 minutes, raised to 420°C in 40 minutes, kept at 420°C for 300 minutes, raised to 470°C in 100 minutes, kept at 470°C for 300 minutes, raised to 600°C in 65 minutes, kept at 600°C for 120 minutes, and finally turned off the power and cooled with the furnace.

[0087] The sintering described in step 4 is specifically to first increase the temperature to 800°C at a heating rate of 5°C / min, then increase the temperature to 1200°C at a heating rate of 3°C / min, and sinter for 2 hours in an air atmosphere, normal pressure and a sintering temperature of 1200°C.

[0088] The component of the ceramic material of this embodiment is fused quartz, the crystal structure is amorphous phase, the dielectric constant ε is 3.42, and the high-temperature dielectric loss tangent tanδ is 0.001. The parameters can meet the basic requirements of wave-transmitting ceramic samples.

[0089] Embodiment 2: This embodiment differs from Embodiment 1 in that: in step 1, 72 parts of inorganic wave-transmitting ceramic powder, 13.4 parts of tackifier, 2.6 parts of elastomer, 10.5 parts of lubricant, 0.5 parts of antioxidant and 1 part of coupling agent are weighed by mass. The rest is the same as Embodiment 1.

[0090] Embodiment 3: This embodiment differs from Embodiment 1 in that: in step 1, 72 parts of inorganic wave-transmitting ceramic powder, 10.1 parts of tackifier, 1.9 parts of elastomer, 14.5 parts of lubricant, 0.5 parts of antioxidant and 1 part of coupling agent are weighed by mass. The rest is the same as Embodiment 1.

[0091] Embodiment 4: This embodiment differs from Embodiment 1 in that: in step 1, 72 parts of inorganic wave-transmitting ceramic powder, 14.4 parts of tackifier, 2.8 parts of elastomer, 9.3 parts of lubricant, 0.5 parts of antioxidant and 1 part of coupling agent are weighed by weight. The rest is the same as Embodiment 1.

[0092] Figure 1 This is the shear rate-viscosity curve of the pellets prepared in step 2 of Example 1 at 170° C. It can be seen from the figure that as the shear rate increases, the viscosity of the ceramic formulation decreases, which means that the material can be extruded smoothly at a high shear rate.

[0093] Figure 2This is the shear strain-modulus diagram of the pellets prepared in step 2 of Example 1 at 170°C. It can be seen from the figure that during the printing process, the material is in a shear stress environment with a large shear strain. At this time, the storage modulus G' is lower than the loss modulus G", showing fluid properties, ensuring smooth extrusion of the material. After the slurry is extruded, the slurry is in a low shear rate and low shear strain environment. The storage modulus G' of the ceramic slurry is higher than the loss modulus G", showing solid properties, ensuring that the molded body will not flow or collapse, thereby ensuring high printing accuracy and good printability, indicating that the ceramic slurry has good printability and can be used for high-quality molding of high-precision 3D structures.

[0094] Table 1: Different formulations at 170°C (shear rate 8s -1 ) under the viscosity control degree control

[0095]

[0096] Embodiment 5: This embodiment is different from Embodiment 1 in that: in step 3, under the conditions of nozzle diameter of 0.8 mm, nozzle temperature of 170° C., hot bed temperature of 75° C., cooling rate of 20° C. / min to 25° C. / min and printing speed of 40 mm / s, 3D printing is performed using pellets to obtain a ceramic body containing a microstructure. The rest is the same as Embodiment 1.

[0097] Embodiment 6: This embodiment is different from Embodiment 1 in that: in step 3, under the conditions of nozzle diameter of 0.8 mm, nozzle temperature of 170° C., hot bed temperature of 80° C., cooling rate of 18° C. / min to 22° C. / min and printing speed of 30 mm / s, 3D printing is performed using pellets to obtain a ceramic body containing a microstructure. The rest is the same as Embodiment 1.

[0098] Embodiment 7: This embodiment is different from Embodiment 1 in that: in step 3, under the conditions of nozzle diameter of 0.8 mm, nozzle temperature of 170° C., hot bed temperature of 80° C., cooling rate of 22° C. / min to 25° C. / min and printing speed of 30 mm / s, 3D printing is performed using pellets to obtain a ceramic body containing a microstructure. The rest is the same as Embodiment 1.

[0099] The effects of different printing processes on the maximum tilt angle of printing and curing are shown in Table 2.

[0100] Table 2: Optimization of printing process at large tilt angles

[0101]

[0102] Comparative Experiment 1: The difference between this comparative experiment and Example 1 is that in step 3, the printing of the three-dimensional boss structure is cancelled, and only a flat plate substrate with a thickness of 2 mm is used; and in step 4, a flat plate-shaped wave-transmitting ceramic piece is prepared. The rest is the same as Example 1.

[0103] Figure 3 This is a schematic diagram of the structure of the ceramic body containing microstructure prepared in step three of Example 1, a is a schematic diagram of the overall structure, and b is a side view; the angle between any one of the four inclined surfaces of the four-sided pyramid and the bottom surface is 60°, that is, the inclination angle is as high as 60°.

[0104] Figure 4 This is a schematic diagram of the printing direction in step three of embodiment 1; as can be seen from the figure, the printing direction is along the length direction of the substrate, and the boss is located on one side of the substrate during the printing process.

[0105] Figure 5 This is the thermal debinding curve of step 4 of embodiment 1; as can be seen from the figure, the debinding temperature rise is strictly controlled. If the debinding temperature rise curve is unreasonable, the ceramic is prone to cracking and deformation.

[0106] Figure 6 The actual pictures are of the ceramic green body with microstructure prepared in step 3 of Example 1 and the broadband wave-transmitting ceramic special-shaped part with microstructure prepared in step 4, a-1 is the ceramic green body, a-2 is the ceramic special-shaped part after solvent degreasing, thermal degreasing and sintering of a-1, b-1 is the ceramic green body, b-2 is the ceramic special-shaped part after solvent degreasing, thermal degreasing and sintering of b-1; it can be seen from the figure that the ceramic special-shaped part after degreasing and sintering has no cracks and deformation, which is consistent with the design model.

[0107] Figure 7 This is the XRD spectrum of the microstructured broadband wave-transmitting ceramic shaped piece prepared in step 4 of Example 1; it can be seen from the figure that: the quartz ceramic has no obvious crystallization phenomenon after sintering, and the original dielectric properties and wave-transmitting properties of the quartz ceramic can be maintained. If crystallization occurs during the sintering process, the dielectric constant increases and the wave-transmitting performance decreases.

[0108] Figure 8 This is a SEM image of the microstructured broadband wave-transmitting ceramic shaped piece prepared in step 4 of Example 1. It can be seen from the image that the density of the sintered quartz ceramic is relatively good, about 90%, while it is well known in the art that quartz ceramic itself is difficult to sinter to a high density.

[0109] Fig. 9 : The wave transmission rate comparison diagram, (a) is the flat wave-transmitting ceramic piece prepared in the comparative experiment 1; (b) is the special-shaped ceramic piece with microstructure and broadband wave-transmitting prepared in step 4 of the embodiment 1;

[0110] Table 1: Performance comparison between comparative experiment 1 without microstructured wave-transmitting ceramic and example 1 with microstructured wave-transmitting ceramic

[0111]

[0112] The brackets in the table are the frequency bands with an incident angle of 40° and a wave transmittance of more than 70%, and the values ​​outside the brackets are the difference between the two, i.e., the width of the frequency band. As can be seen from the figure and the table, the microstructured broadband wave-transmitting ceramic shaped part prepared in Example 1 has obvious broadband wave-transmitting characteristics and high angular stability.

[0113] Embodiment eight:

[0114] A method for preparing a microstructured broadband wave-transmitting ceramic shaped part is carried out according to the following steps:

[0115] 1. Weighing of raw materials:

[0116] Weigh 85 parts of inorganic wave-transmitting ceramic powder, 5.7 parts of tackifier, 3 parts of elastomer, 5 parts of lubricant, 0.3 parts of antioxidant and 1 part of coupling agent according to mass proportion;

[0117] 2. Preparation of 3D printing ceramic raw materials:

[0118] ① The inorganic wave-transmitting ceramic powder and the coupling agent are ball-milled, mixed and dried to obtain a mixture A;

[0119] ② Mix the weighed tackifier, elastomer, lubricant and antioxidant by internal kneading to obtain a mixture B;

[0120] ③ Adding mixture A to mixture B in 4 times, and performing banburying mixing after each addition to obtain a banburying material;

[0121] ④ The mixed materials are extruded through an extruder, and cut after water cooling to obtain pellets;

[0122] The content of inorganic wave-transmitting ceramic powder in the granules is 85wt.%, and the shear rate is 8s -1 At a temperature of 140°C, the viscosity of the pellets is 1810 Pa·s, and at a temperature of 140°C, the shear strain γ corresponding to the intersection of the storage modulus G' and the loss modulus G" of the pellets is 0.095;

[0123] 3. 3D printing:

[0124] Under the conditions of nozzle diameter of 0.8 mm, nozzle temperature of 140°C, hot bed temperature of 70°C, cooling rate of 25°C / min to 30°C / min and printing speed of 20 mm / s, 3D printing was performed using pellets to obtain a ceramic body containing a microstructure;

[0125] The ceramic body containing microstructure is specifically composed of a substrate and a three-dimensional boss structure, and the three-dimensional boss structure is arranged on the inner wall of the substrate; the substrate is a hollow cone with an open bottom, and the three-dimensional boss structure is a curved boss, which is formed by 10 annular grooves and 12 generatrix direction grooves arranged crosswise, the annular grooves are parallel to the bottom surface, and the generatrix direction grooves are arranged from the top downward along the inner wall of the cone; and the printing direction is from the bottom of the cone to the top of the cone;

[0126] 4. Degreasing and sintering:

[0127] The ceramic green body containing the microstructure is subjected to solvent degreasing, thermal degreasing and sintering in sequence to obtain a broadband wave-transmitting ceramic special-shaped part containing the microstructure;

[0128] The bottom diameter of the hollow cone with an open bottom in the prepared microstructure-containing broadband wave-transmitting ceramic special-shaped part is 160mm, the height is 250mm, and the thickness is 5mm; the height of the three-dimensional boss structure in the prepared microstructure-containing broadband wave-transmitting ceramic special-shaped part is 5mm, and the width of the annular groove and the groove in the busbar direction are both 5mm.

[0129] The inorganic wave-transmitting ceramic powder described in step one is a mixture of ceramic powder and additive powder; the ceramic powder is silicon nitride; the additive powder is a mixture of aluminum oxide and yttrium oxide; and the mass ratio of silicon nitride: aluminum oxide: yttrium oxide is 90:5:5; the median diameter of the inorganic wave-transmitting ceramic powder is 500nm, and the particle size span is 4; the particle size span is specifically calculated according to the following formula: Sw=2.56 / [log(D90 / D10)], wherein Sw is the particle size span, D90 is the particle size corresponding to 90% of the cumulative particle size distribution of the sample, D90=1.2 microns, and D10 is the particle size corresponding to 10% of the cumulative particle size distribution of the sample, D10=0.28 microns.

[0130] The tackifier described in step 1 is a mixture of polyethylene and polypropylene, and the mass ratio of the polyethylene to the polypropylene is 1:1.

[0131] The elastomer described in step 1 is ethylene-vinyl acetate copolymer.

[0132] The lubricant described in step 1 is a mixture of paraffin and stearic acid; the mass ratio of the paraffin to stearic acid is 8:2.

[0133] The antioxidant described in step 1 is antioxidant 2246.

[0134] The coupling agent described in step 1 is isopropyl trioleyl titanate.

[0135] The ball milling mixing described in step 2① is specifically to use anhydrous ethanol as the grinding medium, and the ball-to-material ratio is 2:1 and the rotation speed is 200r / min, and the ball milling mixing is 4h; the banburying mixing described in step 2② is specifically to add it to a polymer banburying machine, and banburying it for 60min at a banburying temperature of 145°C and a stirring speed of 100r / min; the banburying mixing described in step 2③ is specifically to mix it for 30min at a temperature of 145°C and a stirring speed of 100r / min; the pellets described in step 2④ have a diameter of 2.85mm and a length of 3mm.

[0136] The solvent degreasing in step 4 is specifically to immerse in a solvent, and degrease for 2 days at a solvent degreasing temperature of 55° C.; the solvent is kerosene;

[0137] The hot debinding described in step 4 specifically uses boron nitride sintering powder to pre-embed the green body, under air atmosphere and normal pressure, the temperature is raised from room temperature to 250°C in 50 minutes, kept at 250°C for 120 minutes, raised to 320°C in 140 minutes, kept at 320°C for 240 minutes, raised to 400°C in 160 minutes, kept at 400°C for 120 minutes, raised to 420°C in 40 minutes, kept at 420°C for 300 minutes, raised to 470°C in 100 minutes, kept at 470°C for 300 minutes, raised to 600°C in 65 minutes, kept at 600°C for 120 minutes, turned off the power, and cooled with the furnace.

[0138] The sintering described in step 4 is specifically to first heat the temperature to 1200°C at a heating rate of 10°C / min, then heat the temperature to 1800°C at a heating rate of 5°C / min, and sinter for 2 hours in a nitrogen atmosphere, a gas pressure of 3MPa and a sintering temperature of 1800°C.

[0139] The main components of the ceramic material of this embodiment are silicon nitride, aluminum oxide and yttrium oxide. The crystal structure of the ceramic after sintering is that the main crystalline phase is silicon nitride, the dielectric constant ε is 7.5, and the dielectric loss tangent tanδ is 0.005. The parameters can meet the basic requirements of wave-transmitting ceramic samples.

[0140] Fig.10 The three-dimensional effect diagram of the broadband wave-transmitting ceramic shaped part containing microstructure prepared in step 4 of Example 8, (a) is a side sectional view, (b) is a cross-sectional view, (c) is a bottom view, (d) is a front view, and (e) is a top view. In the figure, the numbers 1 to 10 are bosses in the generatrix direction, and the size of the bosses in the generatrix direction changes gradually, and the numbers 11 to 14 are bosses in the annular direction, and the size is consistent.

Claims

1. A method for preparing a microstructured broadband wave-transmitting ceramic shaped part, characterized in that It is carried out in the following steps:

1. Weighing of raw materials: Weigh 70 to 85 parts of inorganic wave-transmitting ceramic powder, 5.7 to 14.4 parts of tackifier, 1.9 to 10 parts of elastomer, 5 to 15 parts of lubricant, 0.1 to 1 part of antioxidant and 0.5 to 1 part of coupling agent according to mass proportion; The inorganic wave-transmitting ceramic powder is a mixture of ceramic powder and additive powder; the ceramic powder is a mixture of one or two of fused quartz and silicon nitride; the additive powder is one or a mixture of several of aluminum oxide, yttrium oxide, boron nitride and microcrystalline glass powder; the mass ratio of the additive powder to the ceramic powder is 1:(8-12); the median diameter of the inorganic wave-transmitting ceramic powder is 200 nanometers to 3 micrometers, and the particle size span is 2-7; The tackifier is one of polyethylene, polypropylene, polystyrene, polyester resin and polylactic acid or a mixture of several thereof; The elastomer is one of ethylene-vinyl acetate copolymer, ethylene propylene diene monomer rubber and ethylene-octene copolymer or a mixture of several thereof; 2. Preparation of 3D printing ceramic raw materials: ① The inorganic wave-transmitting ceramic powder and the coupling agent are ball-milled, mixed and dried to obtain a mixture A; The ball milling mixing is specifically performed with anhydrous ethanol as the grinding medium, at a ball-to-material ratio of (1-6):1 and a rotation speed of 200 r / min-400 r / min, for 1 h-8 h; ② Mix the weighed tackifier, elastomer, lubricant and antioxidant by internal kneading to obtain a mixture B; The mixing and kneading is specifically adding the mixture into a polymer internal mixer, kneading for 30 to 60 minutes at a kneading temperature of 130 to 160 degrees Celsius and a stirring speed of 100 to 200 r / min; ③ Adding mixture A to mixture B in 3 to 5 times, and performing banburying mixing after each addition to obtain a banburying material; The mixing is specifically performed at a temperature of 130°C to 160°C and a stirring speed of 100r / min to 200r / min for 10min to 30min; ④ The mixed materials are extruded through an extruder, and cut after water cooling or air cooling to obtain pellets; The content of inorganic wave-transmitting ceramic powder in the granules is more than 70wt.%; at a shear rate of 8s -1 and the temperature is 120°C to 190°C, the viscosity of the pellets is lower than 2000 Pa·s, and the shear strain γ corresponding to the intersection of the storage modulus G' and the loss modulus G" of the pellets is less than 0.1 under the condition of the temperature being 120°C to 190°C; The pellets have a diameter of 2.7 mm to 2.9 mm and a length of 3 mm to 4 mm; 3. 3D printing: Under the conditions of nozzle diameter of 0.4 mm to 0.8 mm, nozzle temperature of 120° C. to 190° C., hot bed temperature of 50° C. to 90° C., cooling rate of 15° C. / min to 30° C. / min, and printing speed of 20 mm / s to 60 mm / s, 3D printing is performed using pellets to obtain a ceramic body containing a microstructure; The ceramic body containing microstructure is specifically composed of a substrate and a three-dimensional boss structure, and the three-dimensional boss structure is arranged on the side surface of the substrate; and the substrate and the three-dimensional boss structure arranged on the side surface of the substrate are printed from bottom to top during 3D printing, and the maximum protrusion size of the three-dimensional boss structure relative to the side surface is 6 mm, and the inclination angle is 40 to 60°; 4. Degreasing and sintering: The ceramic green body containing the microstructure is subjected to solvent degreasing, thermal degreasing and sintering in sequence to obtain a broadband wave-transmitting ceramic special-shaped part containing the microstructure.

2. The method for preparing a broadband wave-transmitting ceramic shaped part containing a microstructure according to claim 1, characterized in that The lubricant described in step 1 is one of polyethylene wax, polypropylene wax, stearic acid amide, oleic acid amide, paraffin, stearic acid and n-butyl stearate, or a mixture of several of them.

3. The method for preparing a broadband wave-transmitting ceramic shaped part containing a microstructure according to claim 1, characterized in that The antioxidant described in step one is one of 2,6-di-tert-butyl-4-methylphenol, octylated diphenylamine and antioxidant 2246, or a mixture of several of them; the coupling agent described in step one is one of γ-aminopropylmethyldimethoxysilane, isopropyl trioleate titanate, di(octylphenol polyoxyethylene ether) phosphite and 3-methacryloxypropyltrimethoxysilane, or a mixture of several of them.

4. The method for preparing a microstructured broadband wave-transmitting ceramic shaped part according to claim 1, characterized in that The substrate described in step 3 is in the shape of a flat plate, a hollow cone with an open bottom, a hollow hemisphere with an open bottom, or a curved plate; the three-dimensional boss structure described in step 3 is a tetrahedron, a tetrahedron, a truncated cone, or a curved boss; the thickness of the substrate in the microstructure-containing broadband wave-transmitting ceramic shaped part prepared in step 4 is 1 mm to 30 mm; when the three-dimensional boss structure described in step 3 is a tetrahedron, and the top and bottom projections of the tetrahedron are both squares, the bottom projection square side length of the tetrahedron in the microstructure-containing broadband wave-transmitting ceramic shaped part prepared in step 4 is 4 mm to 7 mm, the top projection square side length is 1.5 mm to 4.5 mm, and the bottom projection square side length is ≥ the top projection square side length, the height is 3 mm to 6 mm, and the gap between the bottoms of adjacent tetrahedrons is 1 m m~4mm; when the three-dimensional boss structure described in step three is a tetrahedron, and the bottom projection of the tetrahedron is a square, the bottom projection square of the tetrahedron in the microstructure broadband wave-transmitting ceramic shaped part prepared in step four has a side length of 4mm~7mm, a height of 3mm~6mm, and a gap between adjacent tetrahedron bottoms of 1mm~4mm; when the three-dimensional boss structure described in step three is a truncated cone, and the top and bottom projections of the truncated cone are both circular, the bottom projection circular diameter of the circle in the microstructure broadband wave-transmitting ceramic shaped part prepared in step four is 4mm~7mm, the top projection circular diameter is 1.5mm~4.5mm, and the bottom projection circular diameter is ≥ the top projection circular diameter, the height is 3mm~6mm, and the gap between adjacent truncated cone bottoms is 1mm~4mm.

5. The method for preparing a broadband wave-transmitting ceramic shaped part containing a microstructure according to claim 1, characterized in that The solvent degreasing described in step 4 is specifically to immerse in a solvent, and degreasing for 1 to 3 days at a solvent degreasing temperature of 25°C to 60°C; the solvent is one of ethanol, isopropanol, ethyl acetate, kerosene, cyclohexane and toluene, or a mixture of several of them; the thermal degreasing described in step 4 is specifically to use sintering powder to pre-embed the green body, and thermally degreasing for 24h to 72h at a degreasing temperature of 200°C to 600°C; the sintering described in step 4 is specifically to sinter for 2h to 5h at a sintering temperature of 1200°C to 2000°C.

Citation Information

Patent Citations

  • Metal or ceramic consumable item for FDM 3D printing, preparation method for metal or ceramic consumable item and finished product printing method

    CN105665697A